Pengaruh Gaya Kepemimpinan, Budaya Inovatif, Pengendalian Sistem Kinerja Terhadap Orientasi Enterpreneurship - Rabbani, Muhammad Taha Yassin; Mardalis, Ahmad (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The existence of an organization in performance control aims to analyze the impact of leadership style and cultural culture applied within the organizational culture of the work environment (Hestiana et al., 2023). This study uses a quantitative method approach with a descriptive research type, the purpose of this study is to prove whether there are changes in leadership attitudes, innovative culture, and performance system control for the sustainability of the workforce and the business world. The population in this study were employees who worked in the scope of Micro and Macro class businesses with a sample of 166 people